1966
DOI: 10.1113/jphysiol.1966.sp007849
|View full text |Cite
|
Sign up to set email alerts
|

The reflex response to sinusoidal stretching of soleus in the decerebrate cat

Abstract: SUMMARY1. Soleus muscle in the decerebrate cat was stretched sinusoidally through various distances, at various frequencies while tension and e.m.g. activity were recorded.2. Two patterns of stretch reflex activity were seen. In one, slow stretching led to a large increase in tension, whereas in the other tension increased little during slow stretching, but rose steeply during a more rapid stretch. Intermediate states were also seen.3. Both these reflex patterns were abolished when the fusimotor fibres were bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
1

Year Published

1967
1967
2005
2005

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 23 publications
5
21
1
Order By: Relevance
“…the same result as would an afferent signal whose maximum was earlier in the cycle (Jansen & Rack, 1966;Westbury, 1971).…”
Section: T I H Brown P M H Rack and H F Rosssupporting
confidence: 65%
“…the same result as would an afferent signal whose maximum was earlier in the cycle (Jansen & Rack, 1966;Westbury, 1971).…”
Section: T I H Brown P M H Rack and H F Rosssupporting
confidence: 65%
“…Examination of the raw data confirmed that this pattern was seen in all cases where harmonics of the stretching frequency were present. Studies in the cat have shown similar discrete bursts of activity phase-locked to cyclic stretching which became more probable as the amplitude of the stretch increased (Jansen and Rack 1966;Rosenthal et al 1970) and human studies also have shown EMG traces in which such saturation was apparent (e.g. Brown et al 1982b).…”
Section: Discussionmentioning
confidence: 98%
“…5) there was a phase delay of force on position; the joint then exhibited a negative viscous stiffness, with flexor muscles exerting more force while they were shortening than when they were being forcibly extended. This phase delay of force on position never occurs in a passive mechanical system, and it does not occur when continuously activated mammalian muscles are subjected to sinusoidal movements in this range of frequencies and amplitudes (Rack, 1966); it may be regarded as proof of the reflex response to the movement (Jansen & Rack, 1966;.…”
Section: Discussionmentioning
confidence: 99%